2018
DOI: 10.17718/tojde.382663
|View full text |Cite
|
Sign up to set email alerts
|

Building an Online Community: Student Teachers’ Perceptions on the Advantages of Using Social Networking Services in A Teacher Education Program

Abstract: This inquiry examined student teachers' perceptions on the advantages of using Social Networking Services (SNS) in an English teacher education program at a public university in Jambi, Indonesia to ease the communication, supervision, discussion, and report submissions between supervisors and student teachers. The networking types included in the program are Whatsapp, Telegram, Email, and Google Form. The method of the research was qualitative through using focus group discussions as the technique of collectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 31 publications
(23 reference statements)
8
87
1
2
Order By: Relevance
“…Besides, senior teachers have been also reported to have lack of skill for the Internet use in their instruction (Hatlevik et al, 2017). As other studies (Aslan & Zhu, 2016;Habibi, et al, 2018) reported that the teachers, junior and senior, need to collaborate to create meaningful teaching and learning activities which many teachers don't have the sufficient skills and knowledge. Alazam et al (2012) informed that the skills of the teachers in their studies were low due to age, meaning that there was a positive relationship between teachers' ages and teachers' skills in respect to ICT.…”
Section: Teachers' Skills and Beliefs Of Ict And Its Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, senior teachers have been also reported to have lack of skill for the Internet use in their instruction (Hatlevik et al, 2017). As other studies (Aslan & Zhu, 2016;Habibi, et al, 2018) reported that the teachers, junior and senior, need to collaborate to create meaningful teaching and learning activities which many teachers don't have the sufficient skills and knowledge. Alazam et al (2012) informed that the skills of the teachers in their studies were low due to age, meaning that there was a positive relationship between teachers' ages and teachers' skills in respect to ICT.…”
Section: Teachers' Skills and Beliefs Of Ict And Its Integrationmentioning
confidence: 99%
“…Teachers should have adequate skills in order to integrate ICT into their educational activities. Some studies showed that junior teachers consider themselves as the representation of digital natives or millennials who cannot be separated with the use of ICT on daily basis including in their learning activities (Aslan & Zhu, 2016;Bennett, Maton, & Kervin, 2008;Elstad & Christophersen, 2017;Habibi et al, 2018;Hatlevik, Scherer, & Christophersen, 2017;Valtonenet al, 2015). As teachers teach millennial students, they are required to have knowledge and skills of ICT and its integration in classrooms; however, many students in high school levels believe that the activities are not appropriately carried out (Bennett et al, 2008).…”
Section: Teachers' Skills and Beliefs Of Ict And Its Integrationmentioning
confidence: 99%
“…Notably, computer-mediated virtual environments could alleviate physical and psychological barriers to communication. Students are more self-expressive and demonstrate better reflection skills through in-depth online activities and discussions (Habibi et al, 2018;Young, 2003). In Yang, Chuang, Li and Tseng's (2013) research, Moodle (Note 1), a virtual learning platform, was adopted for individualized instruction of English listening and speaking, as well as CTS, with positive outcomes for language proficiency and all the subscales of thinking competency.…”
Section: Cts and Tii Of English As A Second Language (L2)mentioning
confidence: 99%
“…Webquests (Yang, Tzuo, & Komara, 2011), (b) social networking (Habibi et al, 2018), and facilitated online discussions (Lee & Martin, 2017).…”
Section: Framing the Studymentioning
confidence: 99%